UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN SELF CONTROL MASA AKHIR SISWA SEKOLAH DASAR (STUDI KASUS PADA SISWA KELAS VI SD PUI HAURGEULIS, INDRAMAYU) - Sobrina Sobrina; Ahmad Asrof Fitri (JOEL: Journal of Educational and Language Research, 2023)
The background of this research is the very poor condition of the nation's generation who are increasingly deviating from the philosophy of the nation. The infinite rapid technological development is one of the causes of moral decline especially when the new thing is accepted outright without being wisely filtered. Students are the seeds of the nation future generation. Parents and the community indirectly, hand over the formation of self- control of their children to the school in general and to the Islamic Education teachers in particular. Thus this research takes the title of the effort of Islamic education teachers to enhance self control of students’ final study PAI Teachers' Efforts to Improve Self-Control at the End of Elementary School Students (Case Study on Grade VI Students of SD PUI Haurgeulis, Indramayu. The focus of this research is on the role played by the Islamic Education teachers and their way in shaping students’ self-control. Based on the above explanation, this study aims to find out the efforts made by Islamic Education teachers, the results achieved, as well as the supporting factors and obstacles encountered in increasing the self-control of sixth grade students at SD PUI Haurgeulis, Indramayu. This research uses a descriptive qualitative analysis. To collect the data, the researcher conducted an observation, interview and documentation. Then, the data is analyzed using data reduction, data presentation and data verification. From the results of the study it can be concluded that 1. Efforts made by Islamic Education teachers in increasing the students’ self-control are holding religious activities such as congregational prayers, Al-Qur'an recitals, cults and other religious activities carried out by all students in routine, educators and education are programmed according to the schedule set and arranged by SD PUI Haurgeulis, secondly The results achieved in improving self-control by Islamic Education education teachers at SD PUI Haurgeulis are quite good, it is proven by the reduction in violations committed by the students And the last the supporting factors in improving self control are obtained from all the components of SD PUI and facilities provided by the school, while the inhibiting factors are that there are some students who still do not care about punishments and their environmental conditions are not/good.